2014
DOI: 10.1186/s12915-014-0109-x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome organizations in induced pluripotent stem cells reprogrammed from somatic cells belonging to three different germ layers

Abstract: BackgroundNucleosome organization determines the chromatin state, which in turn controls gene expression or silencing. Nucleosome remodeling occurs during somatic cell reprogramming, but it is still unclear to what degree the re-established nucleosome organization of induced pluripotent stem cells (iPSCs) resembles embryonic stem cells (ESCs), and whether the iPSCs inherit some residual gene expression from the parental fibroblast cells.ResultsWe generated genome-wide nucleosome maps in mouse ESCs and in iPSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…In contrast, mouse pluripotent cells generated through SCNT did not appear to show such memories. However, in this study we found that the chromosomes in SCNT embryos and FZ both tended toward nucleosome loss and more open chromatin architecture within a few hours of reprogramming, especially in the X chromosome; similar changes occur in iPSC reprogramming (Tao et al., 2014, Huang et al., 2015). …”
Section: Discussionsupporting
confidence: 66%
“…In contrast, mouse pluripotent cells generated through SCNT did not appear to show such memories. However, in this study we found that the chromosomes in SCNT embryos and FZ both tended toward nucleosome loss and more open chromatin architecture within a few hours of reprogramming, especially in the X chromosome; similar changes occur in iPSC reprogramming (Tao et al., 2014, Huang et al., 2015). …”
Section: Discussionsupporting
confidence: 66%
“…Key epigenetic modifications of chromatin structure include the positioning of nucleosomes and covalent modifications to histone tails, which regulate the expression of specific genes 7 8 9 . Global maps of nucleosome positions in C. elegans 10 S. cerevisiae 11 12 and humans 13 14 show that nucleosomes are not randomly distributed throughout the genome but are highly organized, particularly at TSSs. Critically, dynamic changes of nucleosome positions have also been observed during the differentiation of mouse ESCs to neural progenitors 15 .…”
mentioning
confidence: 99%
“…A pair reads was treated as a fragment. The fragments were counted and then normalized as fragments (number of fragments in special region) per kilobase per million (FPKM) to calculate the nucleosome occupancy level [28, 29]. For each chromosome, nucleosome fragments were binned in 10-kb intervals.…”
Section: Methodsmentioning
confidence: 99%
“…Nucleosomes within 1 kb of the TSS were collected. The total 2-kb length was binned in 10-bp intervals, and the RPKM value in each bin was calculated to get a profile of nucleosome distribution around the TSS [29]. …”
Section: Methodsmentioning
confidence: 99%